FAKTOR RISIKO KEJADIAN ABORTUS PADA IBU HAMIL DI RSUD CILACAP - Ema Wahyuningrum; Ade Rizki (Universitas Harapan Bangsa Purwokerto, 2014)
ccording to the MOH in 2010, the direct cause of maternal deaths in Indonesia related to pregnancyand childbirth, especially that of bleeding (28%), then that is pre-eclampsia (24%), infection (11%),complications of puerperium (8%), prolonged labor / loss (5%), abortion (5%), and others (14%).Although abortion is not the biggest cause of maternal mortality, but the incidence of this requiresmore attention because abortion can cause complications such as bleeding, perforation, sepsis, andshock which can ultimately lead to maternal death. Hospital Cilacap in the incidence of abortion in2012 as many as 331 cases (12.7%) of pregnant women in 2595, increased in 2013 as many as 355cases (13.8%) out of 2557 pregnant women. The purpose of this study to know the description of riskfactors associated with abortion in pregnant women in hospitals Cilacap in 2013 based on maternalage, parity, history of abortion, and pregnancy spacing. This research method using retrospectivestudy approach. This study uses secondary data taken in August, 2013 in General Hospital Cilacap.Sampling using sampling saturated with the number of 355 respondents. The results showed riskfactors associated with abortion based mostly on the mother's age 20-35 years of age as many as 227pregnant women (63.94%), risk factors associated with abortion based largely on a parity paritymultiparas as many as 154 pregnant women (43.38 %), risk factors associated with abortion based onthe history of abortion mostly occurs in women who have never experienced abortion as many as 241pregnant women (67.88%), and the risk factors associated with abortion based on the distancepregnancy mostly occurs in pregnant women with pregnancy spacing â‰¥2 years of the 177 pregnantwomen (49.85%). Keywords: abortion, pregnant women